The Celebration - Thomas Vinterberg (1998)
A darkly comic journey into forbidden family territory. No one can ignore a person like Danish patriarch Helge Klingenfeldt. So on his sixtieth birthday, a celebration is required. Friends and relatives scurry to the country estate. Eventually, every family's secrets will come out. And since his twin sister's death two months ago, prodigal son Christian is more haunted than usual. The time has come for the darkest family skeleton to be revealed, and it must be done in their father's style - with flair, and malice.